Sport and the Covid-19 Pandemic: A Structuralist Analysis of Key Themes in the UK Mass Media - Giulianotti, Richard; Collison, Holly (Frontiers in Sports and Active Living, 2020)
This paper provides a systematic, detailed analysis of UK mass media online reports and narratives on sport and Covid-19 during the main lockdown period over March-May 2020. A “structuralist thematic” approach is utilized to identify and to map systematically the main themes within the mass media. The research is based on reports and narratives on sport-Covid which featured in five leading online UK mass media outlets. The analysis sets out four underpinning statuses or dimensions of sport: the existential, normative, socio-cultural, and political. These dimensions connect directly and, respectively, to four sets of binary opposite media themes on sport during the Covid-19 lockdown: sport as absence/presence, selfish/altruistic, crisis/escape, and threat/solution. Each theme features several types of media report or commentary (which we term “narrative or substantive strands”) on sport-Covid. The paper examines the four binary opposites, and their various types of media report and narrative, in detail. It concludes by discussing the theoretical contributions and substantive findings from the study, and some areas for future research.